Optimization Proposal for Supply Management Implementing Supply Chain Management and Lean Warehousing in an Alcoholic Beverage Marketing Company of The Retail Sector - Cavero Quispe, Claudia Alejandra (2022)
Nowadays, change is the only constant variable. Therefore, business enterprises should focus more attention on them supply chains. The main contribution of this paper is to show the relation between Lean Warehousing and Supply Chain Management since one is inside the other and they complement each other very well to produce results in the retail sector. In the course of the research, the raised hypothesis was proved since the presented results show a better behavior in a 38.36%, compared to the initial scenario. The results of this research show that retail sector companies must perform appropriate management of their inventories, establish a forecasted demand, and have appropriate warehouse spaces. It was possible to decrease their operations time in a 29.59% and have better management of their resources in a 27.50%. The main objective of this paper is to prove that due to the implementation of engineering techniques in the supply processes that involve warehousing, planning, and inventories, and the subsequent decrease of inefficiency, an alcoholic beverage marketing company optimized its operation in said areas. This research applied a mixed methodology, using direct observation and a discrete event simulation software to optimize complex scenarios (Arena).